Environmental Law, the State, and the People: Examining the Reciprocal Obligations of Protection - Hastiyanto, Febri; Faried, Femmy Silaswaty; Dewi, Nourma (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2025)
Widespread environmental degradation in Indonesia frequently gives rise to conflicts among local communities, the state, and business entities. Although Law No. 32 of 2009 provides a legal framework for resolving environmental disputes, the effectiveness of its implementation remains uncertain. This study examines the efficacy of both litigation and non-litigation mechanisms—particularly mediation and administrative approaches—in addressing such disputes. It also assesses the integration of customary law into the national legal system and identifies critical weaknesses in the enforcement of environmental regulations. Employing a normative legal approach supported by case studies of nine environmental conflict cases, the findings indicate that mediation and administrative legal processes often fail to deliver ecological justice. Moreover, customary law remains insufficiently harmonized with formal legal structures. Weak law enforcement, overlapping institutional authorities, and limited community participation further hinder effective resolution. The study concludes that regulatory reform, the strengthening of customary legal systems, and community empowerment are essential to enhancing environmental dispute resolution in Indonesia.